2005
DOI: 10.1177/0013164404272493
|View full text |Cite
|
Sign up to set email alerts
|

Motivational and Skills, Social, and Self-Management Predictors of College Outcomes: Constructing the Student Readiness Inventory

Abstract: The authors used a rational-empirical approach to construct the Student Readiness Inventory, measuring psychosocial and academic-related skill factors found to predict two important college outcomes, academic performance and retention, in a recent meta-analysis. The initial item pool was administered to 5,970 first-year college students and high school seniors to empirically validate and cross-validate the underlying factor structure. Ten first-order and 3 second-order factors were derived, partially resemblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(157 citation statements)
references
References 64 publications
6
145
0
6
Order By: Relevance
“…Others emphasized on non-cognitive factors to adequately predict which students will succeed or fail in university (Tracey & Sedlacek, 1984;White & Sedlacek, 1986). Some others favor the combination of both to predict academic success at university (Le, Casillas, Robbins, & Langley, 2005;Ting, 1998;Wolfe & Johnson, 1995).…”
Section: Prediction Of College Gpamentioning
confidence: 99%
“…Others emphasized on non-cognitive factors to adequately predict which students will succeed or fail in university (Tracey & Sedlacek, 1984;White & Sedlacek, 1986). Some others favor the combination of both to predict academic success at university (Le, Casillas, Robbins, & Langley, 2005;Ting, 1998;Wolfe & Johnson, 1995).…”
Section: Prediction Of College Gpamentioning
confidence: 99%
“…Research has shown that in-role performance is important to both students and universities. For example, study performance is positively related to degree success and completion rates (e.g., Kirby & Sharpe, 2001;Le et al, 2005;Ryland et al, 1994). Students who focus on in-role performance are more likely to be interested in studying quickly and efficiently.…”
Section: In-role and Extra-role Performance In The University Contextmentioning
confidence: 99%
“…Therefore exploring the concept of commitment within the higher education context has potential benefits to multiple stakeholders. For higher education institutions, student drop-out rates can negatively affect reputation and thus recruitment and funding, and under-performing students are more likely to leave an institution before completing their degree than high performers (e.g., Kirby & Sharpe, 2001;Le, Casillas, Robbins, & Langley, 2005;Ryland, Riordan, & Brack, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Ridder et al, 2012;Moffitt et al, 2011). Similarly, the Academic discipline subscale within the Student Readiness Inventory (Le, Casillas, Robbins, & Langley, 2005) has been shown to improve predictions of college GPA beyond that explained by models with only high school GPA and ACT scores (Kommarraju, Ramsey, & Rinella, 2013).…”
Section: The Importance Of Non-cognitive Characteristics and The Needmentioning
confidence: 99%